Severity of lymphocytic choriomeningitis virus disease in different strains of suckling mice correlates with increasing amounts of endogenous interferon. - Yves Rivière; Ion Gresser; J.-C. Guillon; M T Bandu; Pierre Ronco; L Morel-Marogér; P Verroust (1980)
A marked difference was observed in the severity of disease in lymphocytic choriomeningitis (LCM) virus-infected suckling BALB/c, Swiss, and C3H mice. BALB/c mice had minimal liver lesions and none died, whereas C3H mice had extensive liver lesions and all mice died. An intermediate pattern was oberved for Swiss mice (36% mortality). Although there was no difference in the titers of LCM virus in the plasma or liver between these three strains of mice, there was a marked difference in the amount of interferon produced and the duration of interferonemia. C3H mice produced more interferon than Swiss mice which produced more interferon than BALB/c mice, indicating a direct correlation between the amount of interferon induced by LCM virus and the extent of disease. Inoculation of a potent anti-mouse interferon globulin markedly reduced the incidence of mortality in virus-infected C3H mice. BALB/c mice were as sensitive to the effects of interferon as C3H mice because daily administration of potent interferon preparations did induce disease in this strain. This ensemble of results supports our contention that endogenous interferon is in large part responsible for the manifestaions of acute LCM virus disease in suckling mice.